2011
DOI: 10.1007/s10529-011-0669-6
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the thermostability and enzymatic activity of cholesterol oxidase by site-directed mutagenesis

Abstract: Site-directed mutagenesis was applied to enhance the thermostability and enzymatic activity of cholesterol oxidase (ChOx) isolated from Brevibacterium sp. Three amino acid residues (Q153E, F128L, and S143H) located near the FAD-binding site of the enzyme were substituted based on structural analysis. The specific activity of the two-sites mutant Q153E/F128L increased by 11.6% and the relative activity increased by 47% when grown for 2 h at 50 °C. This mutant is a potential industrial strain for producing ChOx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
5
1
Order By: Relevance
“…The LAB strains in this study were stored in Man–Rogosa–Sharpe (MRS) broth with 15% (v/v) glycerol at −70 °C and cultured in 50 mL liquid MRS for 48 h at 37 °C without shaking, as described previously (Wang et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The LAB strains in this study were stored in Man–Rogosa–Sharpe (MRS) broth with 15% (v/v) glycerol at −70 °C and cultured in 50 mL liquid MRS for 48 h at 37 °C without shaking, as described previously (Wang et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Several studies have reported that enzymatic activity could be improved significantly by site-directed mutagenesis of specific amino acid residues surrounding the active centre or binding site (Kang et al, 2007;Sun et al, 2011;Zhang et al, 2013).…”
Section: Comparison Of the Ability To Produce Pla And The Antifungal mentioning
confidence: 99%
“…Thus, thermal stability modification for lichenase as well as other industrial enzymes, coupled with isolation of thermostable lichenases, has become a research focus during the past few decades [ 5 , 6 ]. Indeed, conventional methods represented by directed evolution, and rational design have contributed to remarkable successes in improving the thermal stability of enzymes [ 7 10 ]. Nonetheless, inferior success frequencies for rational design, as well as time consuming in nature, have limited a broad utilization of these methods [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…To further improve the thermal stability of COX, site direct mutagenesis was applied to the Brevibacterium sp. grown at 50˚C for 2 h. It was observed that three amino acid residues (Q153E, F128L and S143H) located near the FAD-binding site of the enzyme were responsible for an increase in specific activity by 11.6% and 47% of two mutated sites Q153E and F128L, respectively [111]. Further studies on this bacterium showed that 0.15% (w/v) cholesterol emulsified with 0.05% Tween-80 induced the highest amount of COX production in comparison to use of other detergents [112].…”
Section: Stability and Activity Of Coxmentioning
confidence: 99%